1997
DOI: 10.1124/mol.51.4.683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adenophostin-A and Inositol-1,4,5-trisphosphate on ClCurrents inXenopus laevisOocytes

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 48 publications
4
33
1
Order By: Relevance
“…Utilizing Ca 2ϩ -dependent chloride currents as an indirect assay of [Ca 2ϩ ] i changes, both DeLisle et al (8) and Hartzell et al (9) observed activation of Ca 2ϩ entry with low concentrations of adenophostin A (ϳ100 pM (8) and ϳ50 pM (9)). DeLisle et al saw no evidence of Ca 2ϩ release with these concentrations, whereas Hartzell et al observed small chloride currents attributable to intracellular release.…”
Section: Fig 2 Effect Of (245)ip 3 (1 M) Microinjected Into An Oomentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing Ca 2ϩ -dependent chloride currents as an indirect assay of [Ca 2ϩ ] i changes, both DeLisle et al (8) and Hartzell et al (9) observed activation of Ca 2ϩ entry with low concentrations of adenophostin A (ϳ100 pM (8) and ϳ50 pM (9)). DeLisle et al saw no evidence of Ca 2ϩ release with these concentrations, whereas Hartzell et al observed small chloride currents attributable to intracellular release.…”
Section: Fig 2 Effect Of (245)ip 3 (1 M) Microinjected Into An Oomentioning
confidence: 99%
“…Interestingly, two studies performed in Xenopus oocytes (8,9) suggested a site of action for adenophostin A in addition to that on intracellular Ca 2ϩ stores. In both studies, low concentrations of adenophostin A (Ͻ10 nM) appeared to preferentially activate the Ca 2ϩ entry process, although Hartzell et al (9), unlike DeLisle et al (8), could not find a clear dissociation between Ca 2ϩ release and Ca 2ϩ entry.…”
mentioning
confidence: 99%
“…To test this possibility, we injected oocytes with high concentration of IP 3 (B2.5 mM), which results in rapid Ca 2 þ release similar to what is observed with ionomycin, and leads to a large I ClT following store depletion ( Supplementary Fig. 1E) 44,45 . We further treated cells with lysophosphatidic acid (LPA), which is known to activate G-protein coupled receptors and stimulate phospholipase C (PLC) to generate IP 3 in Xenopus oocytes 46 .…”
Section: Differential Activation Of Cacc By Ca 2 þ Mobilizing Agentsmentioning
confidence: 99%
“…These results argue that store depletion with IP 3 enhances the ability of CaCC to respond to Ca 2 þ flowing into the cell through SOCE. To confirm that this effect is specific to IP 3 and SOCE, we activated SOCE with the low-affinity Ca 2 þ chelator, TPEN, which is known to buffer free intraluminal ER Ca 2 þ thus simulating store depletion 44,45 . In a similar manner to thapsigargin and ionomycin, TPEN failed to generate the large I ClT observed following IP 3 df treatment (Fig.…”
Section: Differential Activation Of Cacc By Ca 2 þ Mobilizing Agentsmentioning
confidence: 99%
“…Previous studies have shown this high affinity agonist for the InsP 3 receptor to be particularly effective at depleting agonist-sensitive internal Ca 2ϩ stores and maximally activating store-operated conductances including CRAC (26,27). Preincubation of the cells with either CspA or ascomycin (1 and 5 M, respectively, for 15-30 min) resulted in inward currents through the SOC channels measured at Ϫ80 mV with 400 nM internal Ca 2ϩ of 0.38 Ϯ 0.03 pA/pF (n ϭ 12) and 0.41 Ϯ 0.03 (n ϭ 5) respectively.…”
Section: Calcineurin and The Regulation Of Ca 2ϩ Entry 40092mentioning
confidence: 99%